2002
DOI: 10.20506/rst.21.2.1331
|View full text |Cite
|
Sign up to set email alerts
|

Viral, parasitic and prion diseases of farmed deer and bison

Abstract: Malignant catarrhal fever IntroductionMalignant catarrhal fever (MCF) is the most important viral disease of farmed or ranched bison (Bison bison and Bison bonasus) and deer (7,9,16,20,28,53,80,118,128). The disease, as a clinical entity, is known on all continents and in most countries. At least three types of the virus have been implicated in the disease.The disease is caused by members of the gammaherpesviruses group. Alcelaphine herpesvirus-1 (AHV-1), carried asymptomatically by the wildebeest (Connochaete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 117 publications
1
47
0
Order By: Relevance
“…Nevertheless, the confirmation of the presence of BHV-1 and BRSV in several individuals in such a small number of herds, where the size of the herds ranges from 8 to 12 animals, may indicate the prevalence of these viruses and the possibility of PI individuals, especially since a characteristic trait of the natural behaviour of the European bison, typical for the herd instinct, is migration associated with the search for food, which makes effective and more precise monitoring of the transmission of infections more difficult. As reported by other authors (Haigh et al 2002, Salwa et al 2011, wild ruminants (mule deer, elk and bison) may harbour and transmit the virus without exhibiting significant disease symptoms.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Nevertheless, the confirmation of the presence of BHV-1 and BRSV in several individuals in such a small number of herds, where the size of the herds ranges from 8 to 12 animals, may indicate the prevalence of these viruses and the possibility of PI individuals, especially since a characteristic trait of the natural behaviour of the European bison, typical for the herd instinct, is migration associated with the search for food, which makes effective and more precise monitoring of the transmission of infections more difficult. As reported by other authors (Haigh et al 2002, Salwa et al 2011, wild ruminants (mule deer, elk and bison) may harbour and transmit the virus without exhibiting significant disease symptoms.…”
Section: Resultssupporting
confidence: 51%
“…Moreover, individuals seropositive for BVDV among red deer and roe deer were found to constitute about 10% of the animal population tested. Other reports (Haigh et al 2002) have confirmed the occurrence of various aetiological infectious agents for cattle in the wild ruminants population (European bison, American bison, red deer, chamois, etc.) in the United States, Canada, Australia, New Zealand and European countries.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Besides the ticks from Ixodes ricinus L., 1758 complex, deer keds (Lipoptena cervi L., 1758) are considered as one of the most frequently occurring blood-sucking ectoparasites of cervids in Europe (Haigh et al 2002;Kaunisto et al 2009). After the mating, inside the uterine sac of adult female fly, larva develops and when is ready to pupate, it is extruded out.…”
Section: Introductionmentioning
confidence: 99%
“…Among Hippoboscidae, Lipoptena, Hippobosca, and Melophagus are the three main genera which parasitize mammals (14,18). The deer ked (Lipoptena cervi), the predominant Lipoptena species in Europe, parasitizes cervids (15), whereas the louse fly (Hippobosca equina) parasitizes cows and horses and the sheep ked (Melophagus ovinus) is a permanent ectoparasite of sheep (Ovis aries) (18).…”
mentioning
confidence: 99%